Application of recovery model for benefit of parents - Puspa Liza, Ghazali; Fauzilah, Salleh; Nurul Zawani, Baharazi; Nur Arifah, Amran; Saffiah Aini, Ismail (2016)
Statistic from Ministry of Higher Education stated that the student enrollment to higher education institute are increasing every year from 262,626 enrollments in 2002 to 358,053 enrollments in 2007 by the fact that level of awareness of education has increased. However in the other aspect, in average rate of Malaysian youths literacy aging 15-24 years old is 98.5%. This means that almost 1.5% of Malaysian youths are illiterate. Also include in this illiteracy youth group is children with learning disabilities. Lack of knowledge and awareness cause them to not getting better education. This study will proposed a recovery model of family takaful towards children with learning disability for benefits of parents. As in our concern, the most influenced person towards the learning disability is the parents of the learning disabled children, so that they can have a small consolation through the takaful plan.